COMPARISON OF GONIAL ANGLE BETWEEN PANORAMIC RADIOGRAPHS AND LATERAL CEPHALOGRAMS IN DIFFERENT SAGITTAL FACIAL PATTERNS - Mirza Hammad-; Sarwat Memon; Durreshahwar Agha; Farhan Sheikh (ziauddin University, 2019)
Background: Gonial angle is extensively used in orthodontics for the diagnosis of the growth pattern. Lateral cephalograms and panoramic radiographs both can be used to assess this angle. The aim of the study was to compare gonial angle measured from the panoramic radiograph and lateral cephalogram indifferent sagittal facial patterns. Methods: A comparative cross-sectional study was conducted at the Department of Orthodontics,Ziauddin College of dentistry, Karachi, from January, 2017 to August, 2017. A total of 140 subjects (60 males and 80 females) with ages ranging from 12 to 39 years were included. Sample was further divided into two groups according to their sagittal skeletal pattern, depending upon the angle formed by ANB on lateral cephalogram: i.e; Skeletal Class I: ANB 0-4° and Skeletal Class II with ANB > 4o. Gonial angle was measured on pre-treatment panoramic radiograph and lateral cephalographs of orthodontic patients. Pearson's correlation coefficient was used to see the degree of correlation of gonial angle between panoramic radiograph and lateral cephalogram. Independent sample t-test was used to find difference in gonial angle between panoramic radiograph and lateral cephalogram in different sagittal facial patterns. Results: Mean age of male patients was 15.3±1.3 years and female patients15.4±0.8 years, respectively. There was no statistically significant difference found in gonial angle measured on panoramic radiograph and lateral cephalogram. Conclusion: Panoramic radiography can be used as an alternative tolateral cephalogram to assess the gonial angle in different sagittal facial patterns.